Functionalised h‐BN as an effective lubricant additive in PAO oil for MoN coating sliding against Si3N4 ball. (23rd September 2020) - Liu, Chaolin; Tang, Gongbin; Su, Fenghua; Xu, Xing; Li, Zhujun
Abstract: Hexagonal boron nitride (h‐BN) exhibits great potential for tribological applications due to its attractive 2D layered structure. In this work, functionalised hexagonal boron nitride (f‐BN) was prepared by ultrasonic exfoliation of pristine h‐BN in water and subsequent hydrothermal modification with sodium oleat. Fourier infrared spectra and X‐ray photoelectron spectra analyses showed that long alkyl‐chains were successfully grafted on the surface of f‐BN by modification process. The tribological properties of the as‐prepared f‐BN as lubricant additive in poly‐alpha‐olefin 10 (PAO10) for lubricating MoN coating sliding against Si3 N4 ball were evaluated by a ball‐on‐disc friction tester. The friction coefficient and wear rate of the oil dispersed with 2 mg/mL f‐BN was respectively reduced by 42% and 29% in comparison with the pure PAO10 oil, suggesting that f‐BN was an effective lubricating additive for reducing friction and wear. Finally, the lubricating mechanism of f‐BN dispersed in PAO10 was discussed and proposed.